WATER EROSION TREATMENT LINEAR-VERTEBRATE PLUG - Rashidov Nurbek son of Shermamat,; Temirov Isroil Gulomovich, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Today, the development and application of soil treatment machines with high soil protection energy-resurstejamkor and work performance are at the forefront. 31% of  the  land  is  affected  by  water  erosion,  and  34%  by  wind  erosion,  and  60  crore annually.considering that more than a ton of the fertile layer of soil is washed away, energy-resource-intensive soil treatment, which protects the soil from water and wind erosion, is one of the important tasks for the development of machines and weapons. Sufficiently insoluble soil particles in water contribute to the occurrence of water and wind  erosion,  the  transformation  of  the  soil  surface  into  small  particles  and  the destruction of soil residues,  it leads to a decrease in its ability to collect moisture. Erosion by water and wind absorbs the fertile part of the soil and accelerates the onset of soil drought. The result was a blunderbuss with a butt structure, a shaped warhead, and the ability to withstand a load [1,2]. Data and their assumption: as you know, lalmikor farming occupies an important place in the economy of Uzbekistan. In our republic, lalmikor farmable soils are worth 2 million. 130,000 hectares. The area of the Lalmikor maydans is 801.45 thousand hectares, including the maydans located in the Crimea The Reserve (235.5 thousand ha.), Jizzakh (204.5 thousand ga.) and Samarkand (193.9 thousand ha.) per province. Lalmi farming is done on sloping land in most HAVs[1].